A High Resolution Radio Survey of Class I Protostars - Lucas, P; Blundell, K; Roche, P (2000)
We report the results of a survey of low mass Class I protostars in the cm continuum. In the initial survey, seven sources in the Taurus star formation were observed with the VLA at 0``.25 resolution. All seven sources drive CO outflows and display Herbig-Haro flows in the optical or near infrared wavebands. 4/7 sources were detected, two of which are new discoveries in systems of very low luminosity, one being the lowest luminosity system detected to date in the cm continuum. Notably, three sources were not detected to a 3-sigma limit of 0.10 mJy/beam, which indicates that significant cm continuum emission is not a universal feature of Class I systems with outflow activity. Subsequent observations of HH30, a more evolved Class II system, found no emission to a 3-sigma limit of 0.03 mJy/beam. After comparison with near infrared data, we suggest that the discriminating feature of the detected systems is a relatively high ionisation fraction in the stellar wind. Temporal variability of the outflow may also play a role. The one relatively bright source, IRAS 04016+2610 (L1489 IRS), is clearly resolved on a 0``.4 scale at 2 cm and 3.5 cm. Follow-up imaging with MERLIN did not detect this source with a 0``.04 beam, indicating that the radio emission is generated in a region with a radius of about 25 au, which is broadly similar to the radius of the bipolar cavities inferred from models of near infrared data. Interpretation of this system is complicated by the existence of a quadrupolar outflow, which we originally detected through polarimetric imaging. We present a near infrared H2 image in which a bow shock in the secondary outflow is clearly seen. This complicated structure may have been caused by a gravitational interaction between two protostars.